(x/3)+(3/4)=(x/6)+4

Simple and best practice solution for (x/3)+(3/4)=(x/6)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x/3)+(3/4)=(x/6)+4 equation:



(x/3)+(3/4)=(x/6)+4
We move all terms to the left:
(x/3)+(3/4)-((x/6)+4)=0
We add all the numbers together, and all the variables
(+x/3)-((+x/6)+4)+(+3/4)=0
We get rid of parentheses
x/3-((+x/6)+4)+3/4=0
We calculate fractions
24x^2/()+(-((+x*3*4)/()+()/()=0
We calculate terms in parentheses: +(-((+x*3*4)/()+()/(), so:
-((+x*3*4)/()+()/(
We can not solve this equation

See similar equations:

| x+2x=1.6 | | 2y+6=-12+3y | | 16+6x=52 | | 8.2+7x-11.2=4+6x-x | | 16(v+1)-4v=4(3v+2)-12 | | 2x+16+16/2=5x-24 | | ((2x^2)/25)=18 | | 2|4-3x|=2 | | Y+2y=1.6 | | 5x-27=x+13 | | 2(2w+3)+w=9w | | (2x^2)/25=18 | | 4f=6 | | (7x÷2)-3=18 | | 7x÷2-3=18 | | 12a+6=54 | | -4(3-5x)=48 | | 0.2x+3=0.1+0.7 | | 3x+8=3(x-3)-2 | | 11/9y-12=1 | | 2(-15/4)+4a=7 | | 3(2x-5)-5=3(x-5)+22 | | (x-16)(28)=180 | | 2x=5=3x+1 | | -8x+1/3x-x/3=0 | | 10y+5=405 | | 7x-7=-7(1-x) | | 15-3(4m+6)+14=2m-3 | | 5x(3+2)=86-9 | | V^2+7v-13=-5 | | 10y5=405 | | 2x+5=3x=1 |

Equations solver categories